Analisis Motivasi Kerja Tutor dan Perspektif Dampak Kompensasi Lembaga Bimbel AHE KATEMAS Kudu - Vivi Rahma; Cahyo Tri Atmojo (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
Motivation is the most important part in encouraging people to do various things, the role of this motivation is very well used to increase productivity in society, especially in the workforce. In this study, researchers examined the analysis of tutor work motivation and perspective on the impact of compensation at the AHE Katemas Kudu tutoring institution. This study aims to find out the data and explore the work motivation of tutors and perspectives on the impact of compensation at the AHE Katemas Kudu tutoring institution. This research belongs to the qualitative descriptive research method located in the Kudu area. The subject of this study was the AHE Katemas Kudu tutoring tutor. The data collection technique is to use an interview dialog system with a resource person named Mrs. Sholihah. From the results of interviews with informants, it was found that motivation for employees is not just giving salaries, but the granting of licenses and rewards can also increase welfare and affect the performance of tutors at AHE Katemas Kudu.